Infancy and adolescence mapuche in literatureof the Araucanía - Guillermo Williamson; Isolde Pérez; Francisca Modesto; Guillermo Coilla; Nilsa Raín (Universidad de La Rioja, 2013)
The indigenous infancy and in her indigenous Mapuche is almost invisible in the specialized literature of intercultural bilingual education 135 Contextos Educ., 15 (2012), 135-152 CONTEXTOS EDUCATIVOS, 15 (2012), 135-152 and in general of the education. A review of texts of authors Mapuche and travelers not Mapuche ancient and of historians and current educators, they give tracks and guidelines to describe and to understand the infancy and adolescence current Mapuche. This original people is located in fields and cities of Chile and specially in the south of the country, in the Region of The Araucanía. The article the wise persons' testimony gathers Mapuche and travelling foreigners who narrate his visions on the childhood Mapuche of his epoch. There is done, in addition, a review of some current studies referred to the topic. The article presents and thinks about these visions as contribution to a better comprehension of the children, girls and young women Mapuche who take part of the pedagogic process of the intercultural bilingual education.